Results of monitoring on pacific salmon in the Sakhalin Bay in 2023 - A. V. Mikhailov; Т. N. Mironova; V. О. Morozov (Известия ТИНРО, 2024)
Results of pacific salmon research in the western Sakhalin Bay (Okhotsk Sea) in July-August 2023 are presented. Commercial catches by fixed seines at the mouths of Kol and Tyvlinka Rivers are analyzed with biological analysis of pink and chum salmon spawners. Data on annual catches of the pink and chum salmon in the western Sakhalin Bay (within Khabarovsk Territory) in 2007–2023 are provided.